Key factors for integrated project team delivery: A proposed study in IBS Malaysian construction projects - Mohd Nawi, Mohd Nasrun; Osman, Wan Nadzri; Che-Ani, Adi Irfan (AENSI Journals, 2014)
The existence of Industrialized Building System (IBS) in Malaysian construction industry was started in 1960s. However, the participation of contractor to get involved in the IBS project is currently poor.The previous researchers have identified that one of the main barrier for IBS implementation is because of lack of information and communication among stakeholders involved during the design stage of project life cycle.Accordingly, an integrated team approach was suggested by the construction lead report such as Latham Report 1994 and Egan Report 1998 which were challenge the current industry to migrate from the traditional fragmented approach towards integrated practice.In this research, will focuses on the process of identifying the key factors for the successful integrated team practice.Although the status of this research is still at the initial stage of progress however it is significantly important to be discussed for the further improvement that can be made in the future.